Multi-loop atomic Sagnac interferometry - Christian Schubert (Nature Portfolio, 2021)
Abstract The sensitivity of light and matter-wave interferometers to rotations is based on the Sagnac effect and increases with the area enclosed by the interferometer. In the case of light, the latter can be enlarged by forming multiple fibre loops, whereas the equivalent for matter-wave interferometers remains an experimental challenge. We present a concept for a multi-loop atom interferometer with a scalable area formed by light pulses. Our method will offer sensitivities as high as $$2× 10^{-11}$$ 2 × 10 - 11 rad/s at 1 s in combination with the respective long-term stability as required for Earth rotation monitoring.